Anticorrosive Properties of Chromium Coatings on AISI H13 Steel Produced via Gaseous Nitriding in a Vacuum - Cifuentes Aya, Hector; Olaya, Jhon Jairo (TECCIENCIA, 2018)
This paper shows the results of this process through the performance of a duplex treatment that combines the application a single chromium hard coating Cr(VI) on a AISI H13 steel with a thermochemical treatment of vacuum gas nitriding. The thickness of the electroplated coating was 15 μm, and N2 was used as precursor gas, with a flow of 100 ml/min at a pressure of 1.2 kPa to produce a CrxNy coating. The existing phases were determined by means of X-ray diffraction, and the corrosion resistance was evaluated via potentiodynamic polarization and electrochemical impedance spectroscopy techniques in a three- electrode electrochemical cell. Characterization via XRD determined the presence of chromium nitrides of type Cr2N, with an important orientation along the plane (300) associated with the partial pressure of N2 and the thermodynamic behavior. The corrosion resistance results showed a significant decrease in the corrosion current density compared with those exhibited by samples chromed by electroplating with AISI H13 steel without nitriding. These results, coupled with the sealing of characteristic microcracks of the electroplated chrome coating, could improve the corrosion resistance, because of the existence of the CrxNy phase.